The effect of pad, capital expenditures, government size, and budget changes on regional financial performance (in central java province in 2019-2021) - Bunga Widya Safitri; Novi Dirgantari; Eko Hariyanto; Dwi Winarni (Trigin Publisher, 2023)
The pandemic due to Covid19 has an impact on the budget policies of local governments of regencies/cities in Central Java which has resulted in a decrease in regional financial performance. The purpose of this study examines the effect of Regional Original Income, Capital Expenditure, Government Size, and Budget Changes on the Financial Performance of Regencies and Cities in Central Java Province in 2019-2021. The sampling technique used was saturated samples, so that 35 district and city governments in Central Java were obtained. The research method used is Quantitative. The analysis technique uses multiple regression analysis. The results showed that the Variables of Regional Original Income and Government Size had a positive effect on regional financial performance while the Capital Expenditure Variables and Budget Changes had a negative effect on regional financial performance.%MCEPASTEBIN%